Analisis Keberlanjutan Dan Peran Csr Dalam Pengembangan Ekonomi Lokal - Sabolak, Yohana; Zebua, Foniaman (CV. SINAR HOWUHOWU, 2024)
Local economic development is an important aspect in the context of sustainability, where the role of Corporate Social Responsibility (CSR) has great potential to make a significant contribution. CSR not only plays a role in fulfilling corporate social responsibility, but also serves as a catalyst for sustainable economic growth. This paper analyzes the role of CSR in the context of local economic development, focusing on its practical implementation and its impact on communities and the environment. Through an in-depth approach to case studies and related literature, this research explores CSR strategies that are effective in integrating local economic needs with sustainable practices. The results of the analysis show that the integration of CSR in local economic development not only strengthens the relationship between companies and communities, but also increases local capacity to be economically and environmentally sustainable. The implications of this research provide a deeper understanding of how CSR can play a role in supporting sustainable local economic development in the future.